Measurement and Prediction of the Adsorption of Binary Mixtures of Organic Vapours on Activated Carbon - Jufang Wu; Zili Xie; Kunmin Guo; Ola Claesson (Adsorption Science & Technology)
This paper describes a modified headspace method for measuring the adsorption equilibrium of mixtures of organic vapours. The advantage of the method relative to the ordinary headspace method is the shorter time needed to reach adsorption equilibrium. The adsorption isotherms of benzene, hexane and pentane on activated carbons were acquired quickly and easily using this method. The method has also been used to measure the binary equilibrium data of benzene–hexane, benzene–pentane and hexane–pentane mixtures on three types of activated carbon. The ‘Ideal Adsorbed Solution Theory’ (IAST) was used to predict the binary adsorption equilibria from the adsorption isotherms for the single components. Good agreement was obtained between prediction and measurement for the total amount of components adsorbed, as well as for the ratio of compounds in the adsorbed phase. The small deviation noted was probably a result of using the Freundlich adsorption isotherm in IAST modelling.